Serum ferritin observations in beta thalassemia major patients with dermatological manifestation - Chakrabarty, Tonusree; Khatun, Ayesha; Saha, Subarna; Urmi, Aklima A.; Hossain, Fatema; Bhattacharjee, Pranab; S. Gupta, Amit; Saha, Susmita (International Journal of Research in Medical Sciences, 2024)
Background: Beta thalassemia major is a severe inherited blood disorder requiring regular blood transfusions, leading to chronic iron overload. This study aims to analyze serum ferritin levels and their association with dermatological manifestations in patients with beta thalassemia major in Bangladesh. Methods: This cross-sectional observational study was conducted at the Department of Transfusion Medicine, Bangabandhu Sheikh Mujib Medical University, Dhaka, from March 2019 to August 2021. A purposive sample of 60 beta thalassemia major patients was selected based on specific inclusion and exclusion criteria. Data collection included detailed medical histories, dermatological examinations, and laboratory investigations for serum ferritin levels. Statistical analysis was performed using statistical package for the social sciences (SPSS)-27. Results: Among the participants, 26.67% were aged 10 years or younger, and 46.67% were aged 11-20 years. The gender distribution was 43.33% male and 56.67% female. The mean hemoglobin level was 6.17±0.95 g/dl, with 75.00% of participants exhibiting extremely high serum ferritin levels (>1000 ng/ml). Dermatological manifestations included hyperpigmentation (50.00%), xerosis (46.67%), and pallor (26.67%). Significant associations were found between high serum ferritin levels and conditions such as hyperpigmentation (p=0.028) and xerosis (p<0.001). Conclusions: The study underscores the critical need for regular monitoring and effective management of serum ferritin levels to mitigate dermatological and systemic complications in beta thalassemia major patients. Effective chelation therapy is essential to reduce the iron burden and improve patient outcomes.